Performance of Convolution Codes Based on 60 GHz Inter-Chip Wireless Interconnection System - Xuehua Li; Siyu Shen; Yafei Wang (Dianxin kexue)
In order to solve reliability problem in 60 GHz inter-chip wireless interconnection system，the performance of convolution codes was studied from the view of coding gain and energy consumption. The characteristics of CM7.2 channel and received signa1-to-noise ratio（SNR）were analyzed. Combining with channel coding theory，the critical distance was deduced，which was seen as the energy efficiency standard of coding system. On the basis of theoretical research，the maximum communication distance was calculated according to the coding gain which was simulated by MATLAB and the critical distance was achieved according to the circuit energy consumption which was evaluated by QuartusⅡ. Comprehensive considering the coding gain，the energy consumption and the critical distance of convolution codes，the priority coding scheme was proposed，which provided a kind of ECC technical reference for 60 GHz inter-chip wireless interconnection system and other 60 GHz short-range wireless communication systems.